Alleviating Shoulder Pain and Enhancing Scapular Joint Range of Motion in Avabahuka (Frozen Shoulder) through Marma Chikitsa: A Case Study - Verma, Hemendra Kumar; Dhabhai, Neelam; Sharma, Mahendra Kumar (International Research Journal of Ayurveda & Yoga, 2025)
Frozen shoulder, medically termed adhesive capsulitis, is a debilitating condition that restricts shoulder mobility and causes pain. This ailment is frequently linked to medical conditions such as diabetes and hypothyroidism. This case study explored Marma Chikitsa, an Ayurvedic treatment, as an alternative to conventional pharmacological and physiotherapy interventions. A 31-year-old male with persistent right shoulder pain and rigidity who was unresponsive to NSAIDs and physiotherapy underwent treatment with Marma Chikitsa. Therapy involved applying pressure and gently stimulating specific Marma points on the shoulder twice daily. Pain assessment done by using the NRS-11 scale and goniometric measurements of shoulder function were performed. After treatment, the patient’s pain decreased from 7 to 1 on the NRS-11 scale, with significant improvements in shoulder movement: abduction increased from 60° to > 160°, flexion from 70° to >160°, and extension from 30° to 60°. Marma Chikitsa may improve energy and blood circulation, promote muscle relaxation, and reduce pain in frozen shoulder patients. This non-invasive, integrative approach offers a safe, effective, and affordable alternative to traditional interventions, showing promise as a potential treatment and management method for frozen shoulder. Adhesive capsulitis, commonly referred to as frozen shoulder, is a disabling condition marked by shoulder joint stiffness and discomfort, resulting in limited range of motion (ROM).[1] This condition, referred to as “Avabahuka” in Ayurvedic medicine, significantly affects an individual’s quality of life and daily activities.[2] While conventional treatments such as physical therapy, corticosteroid injections, and, in severe cases, surgical interventions are commonly employed,[3,4] there is growing interest in alternative approaches, particularly those rooted in traditional medical systems.[5]